2021
DOI: 10.1096/fasebj.2021.35.s1.05280
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Role of Eaf1 in the Delicate Balance of Lipid Droplet Synthesis and Membrane Composition in Saccharomyces cerevisiae

Abstract: The yeast lysine acetyltransferase, NuA4, is known to be critical important to regulating a variety of cell functions through acetylation of protein targets, resulting in changes in localization, function and/or abundance of its target proteins. Most recently, we have discovered a fascinating role for NuA4 in establishing the balance between lipid droplet formation and phospholipid availability for organelle and cell membranes. This was first discovered upon deletion of the main scaffolding subunit of NuA4 whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have revealed the functions and molecular characteristics of EAF1/2 in Arabidopsis (Dabas et al 2021 ; Scott et al 1999 ), Saccharomyces cerevisiae (Laframboise and Baetz 2021 ; Sweta et al 2021 ), Caenorhabditis (Cai et al 2011 ) and mammalian cells (Kenner 2014 ), such as in cell growth (Dabas et al 2018 ), cell immortalization (Dimartino et al 2000 ) and in melanoma and leukemogenesis (Luo et al 2001 ; Polak et al 2003 ). It has been reported that EAF1/2 can act as transcriptional suppressors to inhibit the TGF-β signaling pathway and WNT/β-catenin signaling in the formation of the three germ layers and the anterior and posterior pattern during early zebrafish embryogenesis (Liu et al 2009 ; Liu et al 2017 ; Liu et al 2018 ; Liu et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed the functions and molecular characteristics of EAF1/2 in Arabidopsis (Dabas et al 2021 ; Scott et al 1999 ), Saccharomyces cerevisiae (Laframboise and Baetz 2021 ; Sweta et al 2021 ), Caenorhabditis (Cai et al 2011 ) and mammalian cells (Kenner 2014 ), such as in cell growth (Dabas et al 2018 ), cell immortalization (Dimartino et al 2000 ) and in melanoma and leukemogenesis (Luo et al 2001 ; Polak et al 2003 ). It has been reported that EAF1/2 can act as transcriptional suppressors to inhibit the TGF-β signaling pathway and WNT/β-catenin signaling in the formation of the three germ layers and the anterior and posterior pattern during early zebrafish embryogenesis (Liu et al 2009 ; Liu et al 2017 ; Liu et al 2018 ; Liu et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%